2004
DOI: 10.1074/jbc.m402059200
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Tristetraprolin mRNA Is Regulated by Mitogen-activated Protein Kinase p38 and by Tristetraprolin Itself

Abstract: Tristetraprolin (TTP) is an mRNA-destabilizing protein that negatively regulates the expression of proinflammatory mediators such as tumor necrosis factor ␣, granulocyte/macrophage colony-stimulating factor, and cyclooxygenase 2. Here we investigate the regulation of TTP expression in the mouse macrophage cell line RAW264.7. We show that TTP mRNA is expressed in a biphasic manner following stimulation of cells with lipopolysaccharide and that the second phase of expression, like the first, is dependent on mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 66 publications
9
147
0
Order By: Relevance
“…ERK1/2 inhibition was also associated with a considerable stabilization of CXCL8 transcript, which, however, could not counteract its suppressive effect on CXCL8 gene transcription, eventually leading to a reduced CXCL8 expression. Most of the studies that analyzed the role of MAPKs on gene transcript turnover have implicated p38 MAPKs or JNKs as relevant contributors to mRNA stability (41,42). Accordingly, we observed that p38␣␤ MAPK inhibition was associated with a reduced stability of both CXCL8 and CCL2 transcripts, hence opposing chemokine expression both at the transcriptional and posttranscriptional level.…”
Section: Discussionmentioning
confidence: 49%
“…ERK1/2 inhibition was also associated with a considerable stabilization of CXCL8 transcript, which, however, could not counteract its suppressive effect on CXCL8 gene transcription, eventually leading to a reduced CXCL8 expression. Most of the studies that analyzed the role of MAPKs on gene transcript turnover have implicated p38 MAPKs or JNKs as relevant contributors to mRNA stability (41,42). Accordingly, we observed that p38␣␤ MAPK inhibition was associated with a reduced stability of both CXCL8 and CCL2 transcripts, hence opposing chemokine expression both at the transcriptional and posttranscriptional level.…”
Section: Discussionmentioning
confidence: 49%
“…Recent studies have shown that the p38 MAPK pathway in particular plays an important role in posttranscriptional regulation that leads to mRNA stabilization (41). The p38 MAPK pathway also strongly induces and activates TTP, which down-regulates TNF␣ (42)(43)(44)(45). Those studies suggested that the p38 MAPK pathway may play a crucial role in regulating the expression of TNF␣ (involving a TTPdependent mechanism); however, the precise mechanism is not completely understood, and less is known about the relationship between TIS11B and the p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of phosphorylation on mRNA ARE binding activity of TTP [3,12,52], phosphorylation may have other functional consequences on the protein, including TTP's stability [33,52,53], autoregulation [32,64], and subcellular localization [51,53]. Phosphorylation of TTP may also affect its association with exosome [65], stress granule [36], nucleoporin CAN/Nup214 [66], and retroviral Tax oncoproteins [67].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%